Interactions of Bacillus licheniformis ATCC 10716 and Normal Flora of Human Skin - Bibel, D. J. (1978)
To determine whether antibiotic production might be ecologically advantageous in the survival of Bacillus species on human skin, we applied spores of a bacitracin-producing strain of Bacillus licheniformis (ATCC 10716) to the forearms of 11 volunteers. Three additional strains of B. licheniformis which did not synthesize antibiotics, including a mutant of ATCC 10716, were used in subsequent control trials. Samples of flora were taken from inoculated and control (opposite forearm) sites during the colonization period, generally 3 weeks. Although population densities were unaltered, changes in the carriage, composition, and bacitracin sensitivity of resident flora were related with the presence of ATCC 10716 only, which suggests that microbial interactions are important in bacillus colonization and in maintenance of normal flora. Interactions were examined in vitro by comparing growth curves of representative skin bacteria, including isolates of Staphylococcus epidermidis, Staphylococcus saprophyticus, Micrococcus luteus, and a large-colony diphtheroid, grown individually, in mixed culture with each other, and together in presence of each test strain of B. licheniformis. We observed some diminution of growth of M. luteus and the diphtheroid in the first mixed culture, and the diphtheroid was completely retarded in common culture with ATCC 10716. Lesser antibiotic effects were seen on the cocci, whose rank of sensitivity was similar to that in vivo. The growth of the diphtheroid was enhanced in mixed culture with those strains of bacilli which lack antibiotic activity.